Leisure-Time Physical Activity Is Associated With Reduced Risk of Dementia-Related Mortality in Adults With and Without Psychological Distress: The Cohort of Norway - Zotcheva, Ekaterina; Selbæk, Geir; Bjertness, Espen; Ernstsen, Linda; Strand, Bjørn H. (Frontiers in Aging Neuroscience, 2018)
Background: Leisure-time physical activity (PA) has been proposed as a protective factor against dementia, whereas psychological distress is associated with an increased risk of dementia. We investigated the associations of leisure-time PA and psychological distress with dementia-related mortality, and whether the association between leisure-time PA and dementia-related mortality differs according to level of psychological distress. Methods: 36,945 individuals from the Cohort of Norway aged 50-74 years at baseline (1994-2002) were included and followed up until January 1st 2015. Leisure-time PA and psychological distress were assessed through questionnaires, whereas dementia-related mortality was obtained through the Norwegian Cause of Death Registry. Adjusted Cox regression analyses were used to estimate hazard ratios (HR) and 95% confidence intervals (95%CI). Results: Compared to inactivity, leisure-time PA was associated with a decreased risk of dementia-related mortality; low intensity leisure-time PA (HR=0.73, 95%CI 0.59-0.89); high intensity leisure-time PA (HR=0.61, 95%CI 0.49-0.77). A statistically significant difference in dementia-related mortality risk was observed between low and high intensity leisure-time PA (p<.05). Psychological distress was associated with an increased risk of dementia-related mortality (HR=1.45, 95%CI 1.16-1.81). Among non-distressed, leisure-time PA was associated with a decreased dementia-related mortality risk; low intensity leisure-time PA (HR=0.77, 95%CI 0.61-0.97); high intensity leisure-time PA (HR=0.65, 95%CI 0.51-0.84). The same applied for those with psychological distress; low intensity leisure-time PA (HR=0.57, 95%CI 0.35-0.94); high intensity leisure-time PA (HR=0.42, 95%CI 0.22-0.82). The interaction between leisure-time PA and psychological distress on dementia-related mortality was not statistically significant (p=0.38). Conclusions: Participating in leisure-time PA was associated with a reduced risk of dementia-related mortality, whereas psychological distress was associated with an increased risk of dementia-related mortality. Leisure-time PA appears to be equally strongly related with dementia-related mortality among those with and without psychological distress, underlining the importance of leisure-time PA for various groups of middle-aged and older adults.